(untitled) (Eurasian Scientific Herald, 2023)
As outlined in the October 2023 report by the International Monetary Fund (IMF), projections indicate an anticipated deceleration in global economic growth for the upcoming year. This trend is attributed to the sustained enforcement of stringent monetary policies on a global scale, amidst the challenges posed by elevated global inflation